New Perspectives on Investment in Infrastructures - Wetenschappelijke Raad voor het Regeringsbele (WRR Verkenningen, 2008)
Over the last two decades most infrastructures were subject to significant regime change. Once a state monopoly, infrastructures have now been liberalised or even fully privatised, thereby introducing new actors and new levels of decision making. Regime change has led to an increased emphasis on service delivery, lower prices and enhanced consumer choice, together with a greater concern for efficiency. What are the effects of regime change and the resultant short-term focus for the long-term investment in physical infrastructures? The essays in this bundle analyse the effects on long-term investment in different infrastructures and from different perspectives and disciplines. These findings form the basis for the accompanying WRR Report entitled "http://www.aup.nl/do.php?a=show_visitor_book&isbn=9789053566053">Infrastructures: Time to invest, in which strategic policy orientations are developed that serve short-term values such as efficiency and service provision, as well as long-term values such as security of supply, innovation and sustainability.